Channel kultura TV CCP's video series on Philippine broadcasting as a cultural force - Del Mundo, Clodualdo, Jr; Del Mundo, Clodualdo, Jr; Roa, Boots Anson; Salvador, Eva Mari G. (Cultural Center of the Philippines, 2003)
A video documentary on the history of Philippine television.